African malaria mosquito Anopheles gambiae Giles (Insecta: Diptera: Culicidae) - Sabrina A. White; Phillip E. Kaufman (EDIS, 2014)
Anopheles gambiae Giles is commonly called the African malaria mosquito because it is the most efficient vector of human malaria in the Afrotropical Region. They are considered to be one of the world’s most important human malaria vectors because of their susceptibility to the Plasmodium parasite, their preference for humans as a host, and their indoor-feeding behavior. Due to their short development time and their preference for developmental habitats near human dwellings, Anopheles gambiae are considered effective vectors of human malaria, as well as lymphatic filariasis (elephantiasis). This 6-page fact sheet was written by Sabrina A. White and Phillip E. Kaufman, and published by the UF Department of Entomology and Nematology, September 2014.